Предмет: Алгебра, автор: gajdusenkovitalik08

Добведіть тотожність.Даю 40 балов.Срочно​

Приложения:

Ответы

Автор ответа: sangers1959
0

Объяснение:

1. Упростим выражение в скобках.

\displaystyle\\\frac{3}{x+3}+\frac{x^2+9}{x^2-9} -\frac{3}{3-x} =\frac{3}{x+3}+\frac{x^2+9}{(x+3)(x-3)} +\frac{3}{x-3} =\\\\\\\frac{3*(x-3)+1*(x^2+9)+3(x+3)}{(x+3)(x-3)}=\frac{3x-9+x^2+9+3x+9}{(x+3)(x-3)}  =\frac{x^2+6x+9}{(x+3)(x-3)}

2.

\displaystyle\\\frac{x^2+6x+9}{(x+3)(x-3)} *\frac{x-3}{x^2+6x+9} =\frac{(x^2+6x+9)(x-3)}{(x+3)(x-3)(x^2+6x+9)} =\frac{1}{x+3}.

Похожие вопросы